Determinants of infant care practices in Minangkabau ethnic - Masruli Masruli; Hari Basuki (Indonesian Pediatric Society, 2012)
Background Child care practices are important for growthand development, and are influenced by cultural determinants.Indicators of infant care practices have not been determined forthe Minangkabau ethnic group.Objective To determine indicators of infant care among aMinangkabau ethnic community.Methods A crossô€ˆsectional study was done in Solok, WestSumatera, a region populated by largely Minangkabau ethnicgroups. Infant feeding care (IFC), infant health care (IHC), infantclean care (ICC), and infant psychosocial stimulation care (IPSe)were the components of infant care used as indicators. Data onthese four components were obtained through interviews withparents and direct observation. A score was assigned to eachcomponent. We used the confirmatory factors analysis (CFA)method to determine whether the indicators were valid in thestudied population.Results We enrolled 417 infants in the study, v.ith a mean age of8.7 months, and 51.6% were female. IFC scores were fairin 72.7%,high in 20.4%, and low in 6.7%. IHC scores were poor in 25.7%,fair in 58.8%, and good in 15.5%. ICC scores were poor in 0.7%,fair in 42.2%, and good in 58.1 %. IPSC scores were poor in 10.6%,fair in 84.9%, and high in 4.5%. On CFA, ICC contributed least tothe indicator model (A: 0.17). ICC and IPSC had fair contributionsto the model (A: 0.5 and 0.47, respectively). Goodness of fit of themodel was good (P>0.05). Root mean square error approximationwas <0.08 and goodness of fit index was >0.9.Conclusions Infant clean care was the most significant contributorto the infant care practice indicator in the Minangkabau ethniccommunity. Similar studies need to be done in other Indonesianethnic groups. [Paediatr Indones. 2012;52:280,3].